2021
DOI: 10.1108/ijchm-04-2021-0545
|View full text |Cite
|
Sign up to set email alerts
|

Leader knowledge hiding, feedback avoidance and hotel employee outcomes: a moderated mediation model

Abstract: Purpose The purpose of this paper is to develop and test a research model that investigates feedback avoidance behavior (FAB) as a mediator of the impact of leader knowledge hiding (LKH) behavior on creativity and job performance. The model also examines whether leader-follower value congruence (LFVC) moderates the aforementioned mediating linkages. Design/methodology/approach Data were collected from hotel managerial employees in two waves and their superiors in Pakistan. The hypotheses were gauged via macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 79 publications
4
46
0
Order By: Relevance
“…As a result, the observer is more likely to mimic a behavior if a trustworthy role model (e.g., an RL) does so. A previous study revealed that leaders act as prominent role models for workers and may greatly affect their behaviors through social learning processes, which is consistent with SLT (Akhtar et al, 2021).…”
Section: Moderating Role Of Lmxsupporting
confidence: 80%
See 2 more Smart Citations
“…As a result, the observer is more likely to mimic a behavior if a trustworthy role model (e.g., an RL) does so. A previous study revealed that leaders act as prominent role models for workers and may greatly affect their behaviors through social learning processes, which is consistent with SLT (Akhtar et al, 2021).…”
Section: Moderating Role Of Lmxsupporting
confidence: 80%
“…However, there is a need to comprehend how RL affects followers' environmentally beneficial behavior (Liao and Zhang, 2020), such as GI. This research confirms that RL inhibits GI and builds on the work of Su and Swanson (2019), Akhtar et al (2021) by examining how RL influences the conduct of GI. This research also contributes to the literature on leadership by demonstrating how leadership style influences GI.…”
Section: Theoretical Implicationssupporting
confidence: 71%
See 1 more Smart Citation
“…Specifically, given the important role of employees’ perceived importance of hotel service policies, human resource managers should help employees understand the principles more deeply through case-by-case analyses and continuous communication. To ensure employees’ affection toward hotel principles, mangers should construct and maintain an open, pleasant and encouraging atmosphere of interaction (Akhtar et al , 2022; Hoang et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In today’s competitive environment, organizations develop internationally and confront several challenges to achieve their goals. Leadership is the most researched area in management since it is directly important in every aspect of the industry ( Akhtar et al, 2021b ). Educational leaders are required to play a variety of tasks, ranging from educational visionaries to legal overseers ( Bartoletti and Connelly, 2013 ), highlighting the complexity of leadership in the education sector.…”
Section: Introductionmentioning
confidence: 99%